2017
DOI: 10.2174/1389200218666170406120203
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Bowel Disease: New Therapeutic Options in the Post Anti-TNFα Era

Abstract: This paper reviews some of the key aspects of these new drugs, including their mechanism of action, some incipient pharmacokinetic and metabolic data, their efficacy and their safety. These new agents will take on an important role in the coming years in the management of patients with moderate-to-severe forms of inflammatory bowel disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A primary failure to respond to anti‐TNF treatment affects 13–40% of patients with CD and secondary response loss occurs in 23–46% of patients. In other studies, 10–30% of patients with IBD showed no initial clinical benefits after anti‐TNF therapy and more than 50% that had an initial favorable outcome lost the effect over time . In addition, a high proportion of patients with IBD relapse after anti‐TNF treatment is stopped .…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…A primary failure to respond to anti‐TNF treatment affects 13–40% of patients with CD and secondary response loss occurs in 23–46% of patients. In other studies, 10–30% of patients with IBD showed no initial clinical benefits after anti‐TNF therapy and more than 50% that had an initial favorable outcome lost the effect over time . In addition, a high proportion of patients with IBD relapse after anti‐TNF treatment is stopped .…”
Section: Introductionmentioning
confidence: 95%
“…In other studies, 10-30% of patients with IBD showed no initial clinical benefits after anti-TNF therapy and more than 50% that had an initial favorable outcome lost the effect over time. 15,16 In addition, a high proportion of patients with IBD relapse after anti-TNF treatment is stopped. 17,18 The overall risk of relapse after discontinuation was found to be 44% for CD and 38% for UC.…”
Section: Limitations Of Parenteral Administration Of Anti-tnf Agentsmentioning
confidence: 99%